Christmas presents : a novella [large type] - Unger, Lisa, 1970- (Thorndike Press large print dynamic drama., 2023)
Madeline Martin has built a life for herself as the young owner of a thriving business, The Next Chapter Bookshop, despite her tragic childhood and now needing to care for her infirm father. When Harley Granger, a failed novelist turned true crime podcaster, drifts into her shop in the days before Christmas, he seems intent on digging up events that Madeline would much rather forget. She's the only surviving victim of Evan Handy, the man who was convicted of murdering her best friend Steph, and is suspected in the disappearance of two sisters, also good friends of Madeline's, who have been missing for nearly a decade. It's an investigation that has obsessed her father Sheriff James Martin right up until his stroke took his faculties. Harley Granger has a gift for seeing things that others miss. He wasn't much of a novelist, but his work as a true crime author and podcaster has earned him fame and wealth - and some serious criticism for his various unethical practices. Still, visiting Little Valley to be closer to his dying father has caused him to look into a case that many people think is closed - and some want reopened. And he has a lot of questions about the night Stephanie Cramer was killed, Ainsley and Sam Wallace disappeared, and Madeline Martin was left for dead, bleeding out on a riverbank. Since Evan Handy went to jail, three other young women have gone missing, most recently a young college dropout named Lolly. Five young women missing in the same area in a decade. Are they connected? Was Evan Handy innocent after all? Or was there some else there that night? Someone who is still satisfying his dark appetites? As Christmas approaches and a blizzard bears down, Madeline and her childhood friend Badger return to a past they both hoped was dead - to find the missing Lolly and to answer questions that have haunted them both, discovering that the truth is more terrible and much closer to home than they think.